Edukasi Tentang Keputihan Bagi Ibu-Ibu Di Kelurahan Karangmalang, Kecamatan Mijen, Kota Semarang - Yulice Soraya Nur Intan; Istiqomah; Masfiyah; Suparmi Suparmi (Scholar Center, 2022)
Lack of knowledge and personal hygiene behavior is one of the causes of vaginal discharge in women. Vaginal discharge should be treated properly to prevent the infection of reproductive organs and cervical cancer risk. Community service activities (PKM) for mothers in Karang Malang Village, Mijen District, Semarang City, Central Java was conducted to educate the mothers about vaginal discharge, its dangers and prevention efforts. This PKM activity was collaborated with Dharma Wanita members of Semarang City and mothers in Karang Malang Village, Mijen District, Semarang City. The participants of the activity were 35 people. The PKM implementation method is divided into 2 stages, namely (1) education in the form of counseling and (2) free consultation and treatment (if needed). Education via counseling and consultation increased the knowledge of mothers about vaginal discharge. The results of PKM are expected to change the personal hygiene behavior of mothers to prevent vaginal discharge.